The role of inflammasome dysregulation in obstructive and non-obstructive azoospermia: a comparative molecular analysis of blood, tissue, and seminal plasma - Mirghanizadeh Bafghi, Seyyed AmirHossein; Fesahat, Farzaneh; Zare, Fateme; Imani, Maryam; Vahidi, Serajoddin; Ansariniya, Hossein; ZareHoroki, Ali; Hadinedoushan, Hossein (Frontiers in Immunology, 2024)
BackgroundTo address knowledge gaps, this study aimed to investigate the involvement of inflammasomes in the etiology of azoospermia. This study focused on the gene expression of key inflammasome components, including NLR family pyrin domain containing 3 (NLRP-3), CASPASE-1, Interleukin-1β (IL-1β), Interleukin-18 (IL-18), NLR family CARD domain-containing protein 4/ice protease-activating factor (NLRC-4/IPAF), and Absent in melanoma 2 (AIM-2).MethodsWe analyzed gene expression in blood and testicular tissue from patients with obstructive azoospermia (OA) and non-obstructive azoospermia (NOA). Additionally, we compared IL-1β and IL-18 expression levels in seminal plasma samples using the Enzyme-Linked Immunosorbent Assay (ELISA) method. For comparison, blood samples from normospermic (NS) individuals were also genetically evaluated.ResultsOur results indicated significantly higher gene expression of inflammasome components in NOA patients than those in OA patients either in blood or in testicular tissue. Both azoospermic groups exhibited higher mRNA levels of inflammasome genes comparing with those from blood samples of NS men. Seminal plasma samples showed significantly increased levels of IL-1β and IL-18 in NOA patients compared to men with OA. The ROC curve analysis indicated strong and significant predictive power of IL-18, AIM-2 and NLRC-4/IPAF gene expression profiles between NOA vs. NS patients and NOA vs. OA.ConclusionsOur findings highlight the role of hidden chronic inflammation in azoospermia, particularly within the NOA group. This study provides a foundation for further detailed research, which could aid in the development of diagnostic panels to differentiate between various azoospermic groups.